A Correlational Study to Assess The Job Adjustment and Service Attitude of Male Nurses Working in Private Hospitals of Udupi and Mangalore Districts, Karnataka. - N., Geo Sebastia; George, Mariamma V; Shalini (Journal of Health and Allied Sciences NU, 2018)
Purpose of the study : The purpose of the study was to examine the effect of job adjustment on service attitude of male nurses.Background of the problem : The shortage and turnover of nurses is a critical problem worldwide. Many people view nursing as a woman's profession; men have three major gender barriers in the nursing education process such as social isolation, refusal to address individual learning needs and the lack of acknowledgement of men in nursing profession.Methods : A correlational design was adopted. Data were collected from a total of 146 male nurses from Udupi and Mangalore districts, Karnataka in 2013.Findings : Majority of the male nurses 90(60.80%) were between the age group of 20-25years. Out of the 146 subjects 67(43.30%) of them were with the educational qualification of BSc Nursing, 64(42.20%) of them were with GNM qualification, and 15(10.10%) were with PB BSc Nursing. Most 60(40%) of them were with clinical experience of 6 months to one year. Majority 72(48.6%) of them were working in intensive care unit. There was a strong, positive, statistically significant relationship between job adjustment and service attitude(r=0.563, p<0.00), inferring that service attitude is dependent on job adjustment.Conclusion : : The findings show that there was significant relationship between job adjustment and service attitude among male nurses.
Keywords: job adjustment; service attitude; job satisfaction; job performance